Normative Reconstruction of Asset Forfeiture: A Legal Pathway Following Demise of Corruption Suspects - Suhartono, Anang; Panjaitan, Hulman (SIGn Jurnal Hukum, 2025)
The death of a corruption suspect before a final and legally binding court judgment creates a fundamental juridical paradox that paralyzes the Indonesian criminal justice system. On one hand, the state loses its instruments for recovering losses due to its reliance on the conviction-based asset forfeiture paradigm. On the other hand, seized assets are trapped in a state of uncertainty, injuring the public’s sense of justice while simultaneously threatening the civil rights of the heirs. This research aims to analyze this normative vacuum (rechtsvacuüm) critically and, as its culmination, to formulate a concrete, implementable legal reconstruction of law as it ought to be (ius constituendum). Using a normative legal research method grounded in statutory, conceptual, and critical comparative approaches, this study finds that the current juridical dead end is at odds with Radbruch’s three basic legal values: justice, certainty, and utility. As a solution, this research proposes a paradigm shift toward the NCB asset forfeiture model, operationalized through a procedural blueprint in the form of a special civil lawsuit. Based on a critical synthesis of international practices, a hybrid model is designed—termed the “Civil-Based Asset Status Examination”—which adopts the flexibility of the civil law tradition while strictly guaranteeing due process of law. The final result is a concrete normative formulation capable of reconciling the state’s interest in asset recovery with the protection of human rights, while simultaneously offering a progressive step in the renewal of criminal procedure law in Indonesia.